A visual score for pruritus. - Gelmetti, C (European Journal of Pediatric Dermatology, 2006)
The author draws a visual scale in five degrees of pruritus. The patient chooses, among six faces with different expressions, ranging from the smile to the most intolerable pruritus, that one which suits him/her. A comment associated to each face can be used by the physician to help the patient in communicating his/her symptoms as well as possible.